Nondual Awareness and the Whole Person - Paul J Mills PhD; Tiffany J Barsotti M.Th., C.Ht; Judith Blackstone PhD; Deepak Chopra MD; Zoran Josipovic PhD (SAGE Publishing, 2020)
Integrative Health aims to treat the whole person and to do so within the context of whole systems and practices. We raise questions as to what constitutes the whole person and what must be taken into account to support the creation of optimal well-being. We propose that in order to fully account for the whole person, the transcendent aspects of human awareness, the development of which is the goal of many meditative traditions, must be taken into account. "Nondual awareness" is a term increasingly used in the literature to describe a state of awareness that is characterized by the experience of nonseparation, compassion, and love. Well-being in this state does not depend on anything being experienced per se, but it is rather an innate attribute of living in nonduality. For these reasons, nondual awareness can be considered foundational to the realization of the whole person and achieving the state of optimal well-being.